Studi Kajian Aktivitas Perdagangan Internasional - Saragih, Rita; Rangkuty, Dewi Mahrani; Rusiadi (STIKes Ibnu Sina Ajibarang, 2024)
The main benefit of ekspor and impor activities is that they help improve a country's economy, ekspor and impor activities are related to international trade. As ekspor and impor activities increase, there are more regulatory practices that may become barriers to trade. One of these obstacles is exchange rate volatility which affects trading activities both directly and indirectly. Volatility in currency exchange rates can affect trade engagement and also a country's trade balance. This research analyzes the exchange rate and clearly states its impact on the trade balance. The results conclude that exchange rate volatility significantly affects the trade balance in terms of impor and ekspor. Considering the results, the exchange rate is a non-trade barrier and affects foreign trade.